HALYCH CHRONICLE OF THE LATE 18th CENTURY - KAPRAL, Myron (Halych. Scientific work collection, 2018)
The publication introduces into the scientific circle an unknown monument of the chronicles in the early modern period – the Halych chronicle of the late 18th century. The author of the work was the priest of the church of St. Nicholas on the Halych suburb rev. Petro Horbachevskyy (1728–1790). The publication analyzes the circumstances of the creation of the annals, the person of the author, historical records (from Khmelnytsky uprising to 1794), religious phenomena and events, natural disasters, national aspects of the relationship. The Halych chronicle of the late 18th century, written in live Ruthenian (Ukrainian), reflects the national(religious context of the era when priests in Galician lands remained almost the only representatives of the spiritual and intellectual elite of the Ukrainian people.